Concepts for 20th-Century cities: Evolution of Le Corbusier’s urban models and their applicability - Rodríguez-Lora, Juan Andrés; Navas-Carrillo, Daniel; Pérez-Cano, María Teresa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research addresses the different urban planning models proposed by Le Corbusier throughout his professional career. These main models, quantifying up to four and others of lesser importance, show the evolution in the conceptualisation and characteristics that he proposed for the city of the 20th century. Their application to different cities, both interior and coastal, demonstrates the diversity of their urban planning and the adaptability of the models mentioned above to real cases. In this way, an attempt is made to overcome the partial visions usually made of his urban work as a whole.